Two cases of acute‐onset cystoid macular edema and serous retinal detachment associated with combined use of encorafenib and binimetinib for advanced melanoma: A possible confounding risk for drug intolerance - Takumi Hasegawa; Shiro Iino; Misako Fujisaki; Sayuri Okamura; Natsuki Baba; Nami Tanaka; Yuko Takeuchi; Noritaka Oyama; Minoru Hasegawa (Frontiers Media S.A., 2023)
Abstract While combined use of BRAF/MEK inhibitors has elicited dramatic clinical efficacy in incurable melanoma, drug‐associated retinopathy has become an emerging adverse event. We present two Japanese men with advanced melanoma who developed visual impairment due to serous retinal detachments (SRDs) with cystoid macular edema (CME) immediately after initial administration of encorafenib/binimetinib, a BRAF and MEK inhibitor. One case had drug‐intolerable retinopathy on repeat dosing. Both cases were switched to another BRAF/MEK inhibitors, dabrafenib/trametinib, with no recurrence of SRDs. Co‐existing CME may be a confounding risk for the early development of SRDs with encorafenib/binimetinib therapy, providing attention during drug administration.